2016
DOI: 10.1186/s12906-016-1046-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavokawain B induced cytotoxicity in two breast cancer cell lines, MCF-7 and MDA-MB231 and inhibited the metastatic potential of MDA-MB231 via the regulation of several tyrosine kinases In vitro

Abstract: BackgroundThe kava-kava plant (Piper methysticum) is traditionally consumed by the pacific islanders and has been linked to be involved in several biological activities. Flavokawain B is a unique chalcone, which can be found in the roots of the kava-kava plant. In this study, the operational mechanism of the anti-cancer activity of a synthetic Flavokawain B (FKB) on two breast cancer cell lines, MCF-7 and MDA-MB231 was investigated.MethodSeveral in vitro assays were attempted such as MTT, flow cytometry of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 42 publications
2
43
0
1
Order By: Relevance
“…These IC 50 values are, however 6 fold lower than that observed in colorectal cancer (HT-29 and HCT 116 cells), which in fact, is within acceptable concentration limits. In one related study, inhibition of two breast cancer cells by FKB at an IC 50 of 12.3 and 33.8 ÎŒM in MDA-MB231 and MCF-7, respectively were reported [19]. APN on the other hand, have been previously reported to inhibit HCT 116 cells at an IC 50 of 39.6 ÎŒg/mL [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These IC 50 values are, however 6 fold lower than that observed in colorectal cancer (HT-29 and HCT 116 cells), which in fact, is within acceptable concentration limits. In one related study, inhibition of two breast cancer cells by FKB at an IC 50 of 12.3 and 33.8 ÎŒM in MDA-MB231 and MCF-7, respectively were reported [19]. APN on the other hand, have been previously reported to inhibit HCT 116 cells at an IC 50 of 39.6 ÎŒg/mL [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study conducted had shown that FKB induced cell cycle arrest at G2/M phase in HCT116 [16], SK-LMS-1 and ECC-1 [17], 143B and SaOS-2 [18], and MDA-MB231 and MCF-7 [19]. On the contrary, findings in this current investigation seem to suggest that increasing dead cells accumulated at subG0/G1 phase instead, rather than blocking cell progression at G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 studies, comprising 15 in vitro (including 2 in situ; 1 ex vivo), 1 in vivo, and 5 that assessed both models, examined the anticancer effects of FKB. Across these studies, there was unanimous agreement that FKB had antiproliferative ability with the majority of papers reporting induction of G2/M arrest . One paper suggested FKB induced G0/G1 arrest .…”
Section: Resultsmentioning
confidence: 99%
“…One paper suggested FKB induced G0/G1 arrest . Additionally, there was a general consensus that FKB induced apoptosis . Proposed mechanisms included increased expression of pro‐apoptotic proteins, such as PUMA, Bim and Bax expression; decreased expression of anti‐apoptotic proteins, such as survivin and XIAP, ROS production; or increase in caspase 3, 7, 8, and or 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation